2021
DOI: 10.1038/s41467-021-21525-5
|View full text |Cite
|
Sign up to set email alerts
|

An ESCRT-dependent step in fatty acid transfer from lipid droplets to mitochondria through VPS13D−TSG101 interactions

Abstract: Upon starvation, cells rewire their metabolism, switching from glucose-based metabolism to mitochondrial oxidation of fatty acids, which require the transfer of FAs from lipid droplets (LDs) to mitochondria at mitochondria−LD membrane contact sites (MCSs). However, factors responsible for FA transfer at these MCSs remain uncharacterized. Here, we demonstrate that vacuolar protein sorting-associated protein 13D (VPS13D), loss-of-function mutations of which cause spastic ataxia, coordinates FA trafficking in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 54 publications
3
72
0
Order By: Relevance
“…Mutations in VPS13D were recently identified in human neurodegenerative diseases (a new type of autosomal recessive spastic ataxia), and mitochondria in these patients showed severe defects in both morphology and function (Gauthier et al, 2018;Seong et al, 2018). Recent studies showed that VPS13D was localized to various organelle MCSs under diverse metabolic conditions, including the ER-mitochondrial/peroxisomal MCSs under normal conditions and mitochondria-lipid droplet junctions under starvation (Baldwin et al, 2021;Guillen-Samander et al, 2021;Wang et al, 2021). Here, we demonstrated a critical role of VPS13D in the negative regulation of ER-mitochondrial MCSs.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Mutations in VPS13D were recently identified in human neurodegenerative diseases (a new type of autosomal recessive spastic ataxia), and mitochondria in these patients showed severe defects in both morphology and function (Gauthier et al, 2018;Seong et al, 2018). Recent studies showed that VPS13D was localized to various organelle MCSs under diverse metabolic conditions, including the ER-mitochondrial/peroxisomal MCSs under normal conditions and mitochondria-lipid droplet junctions under starvation (Baldwin et al, 2021;Guillen-Samander et al, 2021;Wang et al, 2021). Here, we demonstrated a critical role of VPS13D in the negative regulation of ER-mitochondrial MCSs.…”
Section: Introductionsupporting
confidence: 67%
“…Therefore, multiple pathways may be responsible for the ER-mitochondrial hyper-tethering in VPS13D suppressed cells. Since previous studies showed that VPS13 proteins including VPS13D bind and transfer glycerophospholipids and lipid fatty acids moieties in vitro, VPS13D is a potential lipid transfer protein (Kumar et al, 2018;Wang et al, 2021). One possibility is that the lipid transfer activities of VPS13D may be involved in the regulation of the ER-mitochondrial interactions.…”
Section: Vps13d Suppression Results In Extensive Er-mitochondrial Tetheringmentioning
confidence: 99%
“…VPS13D and TSG101 coordinately regulate the trafficking of the free fatty acid (FFA) between mitochondria and LDs at contact sites in cultured cells. The depletion of VPS13D or TSG101 inhibits FFA trafficking from LDs to the mitochondria based on a BODIPY-conjugated FFA assay [ 64 ]. These recent findings demonstrate the critical roles of VPS13 family proteins in regulating organelle contact, dynamics and biogenesis, as well as autophagy and lipid metabolism, which are vital for cellular function and homeostasis.…”
Section: Mitochondria–er Contact/mitochondrial-associated Membrane (Mam)mentioning
confidence: 99%
“…More recently, a new ESCRT-dependent mechanism by which FAs are trafficked from LDs to mitochondria was described. This was shown to be mediated by the lipid transfer protein VPS13D and the ESCRT protein Tsg101 ( Wang et al, 2021 ). Finally, the observation of LD-mitochondria contact sites in yeast, where β-oxidation takes place solely in peroxisomes ( Pu et al, 2011 ), as well the notion that several lipid metabolic enzymes can localize to both mitochondria and LDs in yeast), indicate that LD-mitochondria contacts likely have lipid metabolic functions beyond channeling of FA for β-oxidation.…”
Section: Fa Metabolic Hubs At Ld-organelle Contact Sitesmentioning
confidence: 99%